A longitudinal observational study on the epidemiology of painful procedures and sucrose administration in hospitalized preterm neonates - Mariana Bueno; Marilyn Ballantyne; Marsha Campbell‐Yeo; Carole Estabrooks; Sharyn Gibbins; Denise Harrison; Carol McNair; Shirine Riahi; Janet Squires; Anne Synnes; Anna Taddio; Charles Victor; et al. (Paediatric & Neonatal Pain, 2024)
Abstract Although sucrose is widely administered to hospitalized infants for single painful procedures, total sucrose volume during the entire neonatal intensive care unit (NICU) stay and associated adverse events are unknown. In a longitudinal observation study, we aimed to quantify and contextualize sucrose administration during the NICU stay. Specifically, we investigated the frequency, nature, and severity of painful procedures; proportion of procedures where neonates received sucrose; total volume of sucrose administered for painful procedures; and incidence and type of adverse events. Neonates <32 weeks gestational age at birth and <10 days of life were recruited from four Canadian tertiary NICUs. Daily chart reviews of documented painful procedures, sucrose administration, and any associated adverse events were undertaken. One hundred sixty‐eight neonates underwent a total of 9093 skin‐breaking procedures (mean 54.1 [±65.2] procedures/neonate or 1.1 [±0.9] procedures/day/neonate) during an average NICU stay of 45.9 (±31.4) days. Pain severity was recorded for 5399/9093 (59.4%) of the painful procedures; the majority (5051 [93.5%]) were heel lances of moderate pain intensity. Sucrose was administered for 7839/9093 (86.2%) of painful procedures. The total average sucrose volume was 5.5 (±5.4) mL/neonate or 0.11 (±0.08) mL/neonate/day. Infants experienced an average of 7.9 (±12.7) minor adverse events associated with pain and/or sucrose administration that resolved without intervention. The total number of painful procedures, sucrose volume, and incidence of adverse events throughout the NICU stay were described addressing an important knowledge gap in neonatal pain. These data provide a baseline for examining the association between total sucrose volume during NICU stay and research on longer‐term behavioral and neurodevelopmental outcomes.